[AR] al-Qadaya al-Dalaliyyah fi Kitab "al-Kamil" li al-Mubarrad: The Semantic Issues in al-Mubarrad’s Book “al-Kamil”. - Ibrahim Youssef, Mohamed Abdelrahman (PENERBIT UNIVERSITI SULTAN ZAINAL ABIDIN, 2025)
Semantics studies are deeply rooted in the Arab and human heritage, in a way that reflects the high level of our ancient scholars in this regard. This is evident in the contributions of the scholars of the principles of jurisprudence, commentators, and encyclopedic authors such as Al-Mubarrad’s book “Al-Kamil fi al-Adab wa al-Lughah”. This research deals with the semantic issues contained in the folds of this work; in order to stand on the semantic issues that abound in this precious literary encyclopedia; in an attempt to clarify the approach adopted by Al-Mubarrad when dealing with several semantic issues, including: polysemy, Arabization, foreignness, context, and others. This aspect has not been addressed by researchers before, according to the sources available to the researcher, and this represents the problem of the current research. The researcher adopted the descriptive approach and reached several results, including: that the semantic issues in the book have captured a great deal of the author's attention, and the author's passion for standing on partial meanings was noted, addressing the linguistic aspects in terms of singular, plural, verbal homonym, and opposites. In addition to referring to Arabic dialects, but he did not care much about the Arabized and the foreign; as he touched on them lightly.